Mongolia : 2015 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Mongolia's medium- to long-term prospects are promising given its large natural resources. In the near term, however, the country continues to face balance-of-payments (BOP) pressures on account of low foreign direct investment and weak commodity prices, as well as expansionary macro policies. Imports have now started to taper off and, with the first phase of the Oyu Tolgoi copper and gold mine now in operation, exports have picked up. The trade balance has thus improved, but the overall BOP remains weak. The executive directors have supported ongoing efforts to foster high, inclusive growth by improving the investment climate, enhancing competitiveness, and promoting economic diversification.